Experimental Study on Partially Replacing Aggregates with Polyethylene Waste in Concrete Pavement (International Journal of Innovative Research in Engineering & Management, 2023)
The management of waste plastics presents  a significant difficulty in both India and globally due to the  escalating consumption of plastics and their extensive  decomposition time, spanning many centuries. Therefore, it  is imperative to employ efficient strategies for the  utilisation of these plastic materials. The primary aim of  this study was to examine the viability of utilising  waste polyethylene waste (PEW) as a partial substitute for  aggregates in the manufacturing of concrete pavement  mixtures. This study utilised cement, sand, coarse  aggregate, and polyethylene waste (PEW). PEW was  utilised as a substitute for aggregates by volume at several  percentages, namely 0%, 10%, 20%, and 30%. The findings  of the study indicate that the substitution of 5% of the  coarse aggregate with PEW waste resulted in an 11%  increase in the 28-day splitting tensile strength of the  concrete pavement mix. Furthermore, the compressive and  flexural strengths of the concrete mix in question exceeded  the minimum compressive and flexural values specified by  the concrete mix guide. Based on the findings of the test  results, it is advised that the utilisation of PEW exceeding  5% of the coarse aggregate composition in the mixture be  employed for the construction of low traffic pavements,  rural roads and pavements. The redesigned pavement  blocks are deemed to have the potential to make a  significant contribution towards the global management of  plastic waste.
Keywords: Polyethylene Waste; Mechanical Properties; Aggregates; Concrete Pavement